MUZAKKI'S EXPERIENCE IN PAYING ZAKAT DIGITALLY THROUGH LAZISMU MEDAN: A PHENOMENOLOGICAL STUDY - Aswin Fahmi; M. Guffar Harahap; Ami Nullah Marlis Tanjung; M Radiansyah (INTERNATIONAL, Journal of Sharia Business Management, 2026)
This study seeks to explore in depth the experiences of muzakki in paying zakat through digital platforms provided by LAZISMU Kota Medan, as well as to understand how they interpret this practice within their religious lives. A qualitative approach with a phenomenological method is employed to capture the subjective perspectives of the participants. Data were obtained through in-depth interviews, observations, and documentation involving muzakki who have used digital zakat services, and were analyzed through stages of data reduction, presentation, and interpretation to uncover essential meanings. The results reveal that accessibility, time saving features, and flexibility are key factors encouraging the adoption of digital zakat. Moreover, trust in the institution particularly in terms of transparency and accountability plays a significant role in shaping users’ sense of comfort. From a religious perspective, most participants believe that the use of technology does not lessen the spiritual value of zakat; instead, it helps them maintain consistency in fulfilling their obligations. Nevertheless, some differences in emotional experience remain when compared to conventional methods, especially regarding the sense of spiritual closeness. The study also shows that muzakki actively interpret and assign meaning to their digital experiences, which are influenced by technological aspects, trust, and religious values. The novelty of this research lies in its phenomenological approach, which brings together technological, psychological, and spiritual dimensions to better understand digital zakat practices. The findings suggest that the development of digital zakat services should not only focus on efficiency but also consider the emotional and spiritual needs of users.